(untitled) (Revista Contexto & Saúde, 2025)
Objective: To evaluate the risk of pressure injuries in neurocritical patients admitted to the intensive care unit, using the Cubbin & Jackson scale. Method: Observational study carried out in the Advanced Support Unit in Neurosurgery of a large hospital, in Recife, Pernambuco, Brazil, from August to December 2022. An instrument with sociodemographic, clinical and social data was used to collect data. application of the Cubbin & Jackson Scale every 24 hours from admission until discharge and/or the appearance of a pressure injury. For data analysis, descriptive and inferential statistics were used. Results: The Cubbin & Jackson scale proved to be a valid instrument when used in neurocritical patients, as it identified both high- and low-risk patients who developed pressure injuries. It was observed that being female, having a neurological disease, having difficulty repositioning in bed and using sedatives had a higher risk of developing pressure injuries. Conclusion: The Cubbin & Jackson scale showed that low-risk patients were subjected to pressure at a higher rate.